Contributions of Muhammad Mahfuz Al-Tarmasiy in the field of Islamic studies - Hussin H.; Ahmad A.R.; Saleh M.H.; Zainol N.Z.N.; Zakaria R. (Science Publishing Corporation Inc, 2024)
Indexed by SCOPUS/ERA